Welfare implications of grain price stabilization: some empirical evidence for the United States. - Konandreas, Panos A.; Schmitz, Andrew (Wiley, 1978)
This empirical study demonstrates that, although United States producers and consumers taken together benefit from policies which would stabilize feed grain prices, this is likely not the case for wheat. The model specifies a U.S. domestic demand relationship for food and feed use, a stock relationship and a foreign demand sector; these are estimated by ordinary and two‐stage least squares methods. The key to the analysis is in testing a well‐known theoretical model in which the desirability of price stabilization largely depends on the source of instability (i.e., whether instability is generated abroad or is created internally).